Cutaneous and Gut Dysbiosis in Alopecia Areata: A Review - Nicole E. Burma; Michele L. Ramien (JID Innovations)
Alopecia areata (AA) is a common, immune-mediated nonscarring alopecia. Breakdown of immune privilege combined with local immune cell infiltration is central to the development of AA; yet, the instigating factors causing immune dysregulation remain elusive. Recent attention has focused on the microbiome in AA, where alterations to the usual composition of healthy microorganisms is observed. This review examines the current evidence for bacterial dysbiosis affecting the scalp and gut of patients with AA and summarizes the potential influence of altered microbial composition on immune dysregulation in AA. Although the literature supports changes to the bacterial composition of patients with AA, a causal link between microbial dysbiosis and AA pathogenesis remains to be established.